QUALITY OF LIFE AND COMMON MENTAL DISORDERS AMONG MEDICAL STUDENTS - Lais Silva dos Santos; Ícaro José Santos Ribeiro; Eduardo Nagib Boery; Rita Narriman Silva de Oliveira Boery (Universidade Federal do Paraná, 2017)
The aim of this study was to evaluate the association between quality of life and common mental disorders among medical students from the State University of Southwest Bahia, Jequié campus. A cross-sectional study was conducted with 115 students (61 male and 54 female students) during the second half of 2016. The prevalence of common mental disorders was 32.2% (n=37). The lowest domain of quality of life among individuals with common mental disorders was the environment, with median of 56.4 (IQ 46.9-68.8), followed by psychological, 56.9 (IQ 50-66.6); physical health, 57.1 (IQ 46.6-67.8); and social relations, 65.5 (IQ 50-83.3). This study estimates that all domains of quality of life were reduced in individuals with suspected common mental disorders; and the final regression model showed the physical health and psychological domains as a protection factor for these individuals.